The increasing importance of Plasmodium ovale and Plasmodium malariae in a malaria elimination setting: an observational study of imported cases in Jiangsu Province, China, 2011–2014. (December 2016) - Cao, Yuanyuan; Wang, Weiming; Liu, Yaobao; Cotter, Chris; Zhou, Huayun; Zhu, Guoding; Tang, Jianxia; Tang, Feng; Lu, Feng; Xu, Sui; Gu, Yaping; Zhang, Chao; et al.
Abstract Background Following initiation of China's National Malaria Elimination Action Plan in 2010, indigenous malaria infections in Jiangsu Province decreased significantly. Meanwhile importedPlasmodium infections have increased substantially, particularlyPlasmodium ovale andPlasmodium malariae . Given the risk for malaria resurgence, there is an urgent need to understand the increase in importedP. ovale andP. malariae infections as China works to achieve national malaria elimination. Methods An observational study of imported malaria cases in Jiangsu Province, China was carried out for the period of 2011–2014. Results A total of 1268 malaria cases were reported in Jiangsu Province from 2011 to 2014. Although importedPlasmodium falciparum cases (n = 1058) accounted for 83.4 % of all reported cases in Jiangsu, P. ovale cases (14, 19, 30, and 46) and their proportion (3.7, 9.6, 8.8, and 13.0 %) of all malaria cases increased over the 4 years. Similarly, P. malariae cases (seven, two, nine, and 10) and proportion (1.9, 1.0, 2.6, and 2.8 %) of all malaria cases increased slightly during this time. A total of 98 cases ofPlasmodium ovale curtisi (47/98, 48 %) andPlasmodium ovale wallikeri (51/98, 52 %) were identified as well. Latency periods were significant among thesePlasmodium infections (p = 0.00). Also, this study found that the latency periods ofP. ovale sp., P. malariae andPlasmodium vivax were significantly longer thanP. falciparum . However, for bothP. ovale curtisi andP. ovale wallikeri infections, the latency period analysis was not significant (p = 0.81). Misdiagnosis of bothP. ovale andP. malariae was greater than 71.5 and 71.4 %, respectively. TheP. ovale cases were misdiagnosed asP. falciparum (35 cases, 32.1 %), P. vivax (43 cases, 39.4 %) by lower levels of CDCs or hospitals. And, theP. malariae cases were misdiagnosed asP. falciparum (ten cases, 35.7 %), P. vivax (nine cases, 32.1 %) andP. ovale sp. (one case, 3.6 %). Geographic distribution of importedP. ovale sp. andP. malariae cases in Jiangsu Province mainly originated from sub-Saharan Africa such as Equatorial Guinea, Nigeria, and Angola. Conclusions Although the vast majority of imported malaria cases were due toP. falciparum, the increase in other rarePlasmodium species originating from sub-Saharan Africa and Southeast Asia should be closely monitored at all levels of health providers focusing on diagnosis and treatment of malaria. In addition to a receptive vector environment, long latency periods and misdiagnosis ofP. malariae andP. ovale sp. increase the risk of re-introduction of malaria in China.